Risk Factors for Work Fatigue in Butler Workers in the Tourism Industry in Bali Province in 2024 - Nurul Istya Magfirah; Baiduri Baiduri (Jurnal Indonesia Sosial Sains, 2026)
Work fatigue is a significant occupational health concern in the tourism industry, particularly affecting butler workers in luxury hotels, villas, and resorts. This study examined the risk factors associated with work fatigue among butler workers in Bali Province's tourism industry in 2024. The research aimed to identify and analyze various factors contributing to work fatigue, including workload demands, working hours, physical work environment conditions, and individual worker characteristics. Butler workers face unique occupational challenges due to high service standards, extended working hours, and the pressure to maintain guest satisfaction in luxury hospitality settings. The study employed a cross-sectional design to assess the relationship between various risk factors and the level of work fatigue experienced by butler workers. Findings revealed that work fatigue among butler workers was significantly influenced by multiple factors including excessive workload, prolonged working hours, physical work environment conditions, and inadequate rest periods. The high prevalence of work fatigue among these workers poses serious implications for both worker safety and service quality. This research contributes to the understanding of occupational health issues in Bali's tourism sector and emphasizes the need for improved occupational safety and health (K3) management systems in hospitality establishments. The findings underscore the importance of implementing fatigue management strategies and regulatory compliance to protect worker well-being while maintaining the quality standards expected in the luxury tourism industry.